Hubungan Pengetahuan Tentang Gastritis Akut Dengan Perilaku Pencegahan Gastritis Akut Pada Mahasiswa Di STIKes Panti Waluya Malang - Andari, Widya; Astutik, Nanik Dwi; Misc, MAN, Sr. Felisitas; Sipollo, Berliany Venny (Jurnal Keperawatan Malang, 2023)
Background: Acute gastritis is an inflammation that occurs on the mucosal surface of the stomach due to an unhealthy lifestyle. Gastritis is often suffered by students.Prevent acute gastritis, can be done by increasing knowledge about acute gastritis and implementing acute gastritis prevention behavior. Objective:To obtain information on the relationship between knowledge about acute gastritis and gastritis prevention behavior Methods:This study used descriptive correlation with a cross-sectional approach. Data were collected by giving a questionnaire containing respondent data, acute gastritis knowledge statements, and acute gastritis prevention behavior statements.The sample in this study was 69 respondents who were taken using probability sampling technique stratified sampling.Data analysis using the Spearman rank test Results:The results of the variable analysis test showed that the average student had knowledge about acute gastritis amounting to 41 people (59.4%) with sufficient categories, and had acute gastritis prevention behavior amounting to 37 people (53.6%) with sufficient categories, so bivariate analysis was carried out using the Spearman rank test with the results of 0.029 (p-value <0.05) there is a relationship between knowledge and gastritis prevention behavior by students. Conclusion:Students' understanding of gastritis can affect gastritis prevention reactions.The higher the level of knowledge about acute gastritis, the better it is to do acute gastritis prevention behavior